An investigation of scheduling and packet reordering algorithms for bandwidth aggregation in heterogeneous wireless networks - Latif, Suhaimi A; Masud, Mosharrof Hussain; Anwar, Farhat; Alam, Md Khorshed (IDOSI Publications, 2013)
Heterogeneous Wireless Network (HWN) is the next generation wireless communication system’s platform where Internet services will be offered and delivered through multiple technologies like WiFi,WiMAX, GSM etc. There are some Internet applications that require high bandwidth and therefore, the bandwidth of an individual interface need to be aggregated to form a high speedy logical link. In this regard,some critical issues like packet loss, packet reordering and delay need to be addressed efficiently. This paper aims to investigate the common scheduling algorithms both adaptive and non-adaptive solutions that have been using in networking and communication field. Packet reordering is common in heterogeneous wireless network that has been evaluated briefly in reorder metrics analysis and reorder delay analysis sections. The challenges of packet reordering are also addressed in this paper. This paper gives a state-of-the-art knowledge of bandwidth aggregation and packet reordering in HWN and it is expected that this investigation will be a milestone for further research.